Teaching Video NeuroImage: Clues in Myoclonus Evaluation: When to Consider Sialidosis. (16th November 2021) - Vélez Gómez, Beatriz; Jesús, Silvia; Macias-Garcia, Daniel; Lechon, Beatriz; Mir, Pablo
Abstract : A 53-year-old woman was presented for the evaluation of visual disturbances, generalized and multifocal myoclonus, and progressive ataxia that began at age 30 years (cf. Video 1). Bilateral cherry-red spots in the macula (figure) and a cortical origin in the EEG-EMG coregistration with back-averaging were observed. Reduced neuraminidase activity in fibroblasts and the homozygous mutation c.403G>A in the NEU1 gene confirmed the diagnosis of sialidosis type I.